TINDAK TUTUR DIREKTIF DALAM FILM TELEPON YANG TAK PERNAH BERDERING - Halinda; Triana, Nabila; Safitri, Melisa; Haliq, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the forms of directive speech acts and their strategies found in the film The Phone That Never Rang. This research uses a qualitative approach with a descriptive method. The data, consisting of characters' utterances in the film that contain directive speech acts, were collected using observation and note-taking techniques. Data analysis was conducted by identifying, classifying, and describing the forms and strategies of speech acts based on pragmatic theory. The results of the study show that the film contains various forms of directive speech acts such as requests, commands, and invitations. The strategies used include direct and indirect strategies, adapted to the context of the utterances and the relationships between characters. These findings indicate that directive speech acts play an important role in developing the storyline and character depiction in the film.